Contract Design with Socially-Attentive Preferences - Philipp Weinschenk (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
The standard agency model assumes that the agent does not care how his decisions influence others. This is a strong assumption, which we relax. We find that, although monetary incentives are effective also with sociallyattentive agents, the principal may optimally set none. This could explain the puzzle that empirically only a fraction of employees experiences monetary incentives. We also show that the principal benefits from having a socially-attentive agent and how she optimally influences her agent's preferences. Furthermore, contractibility of effort does not generally cause the implementation of the efficient effort and may harm the generated surplus. This provides an efficiency argument for regulatory boundaries on employers' control over employees and the content of employment contracts.
Keywords: D82; D91; M52; 330; agency model; socially-attentive preferences; incentives